Eroding the Community in Community Supported Agriculture (CSA): Competition's Effects in Alternative Food Networks in California. Issue 4 (23rd July 2015) - Galt, Ryan E.; Bradley, Katharine; Christensen, Libby; Van Soelen Kim, Julia; Lobo, Ramiro
Abstract: The effects of competition within alternative food networks (AFNs) remain largely unexplored. Using a study of farms that operate Community Supported Agriculture (CSA) programmes in California, the state in the USA with the most CSAs, we empirically examine the effects of competition within alternative food networks. We conducted a statewide survey of CSA farmers in California, which collected data from 111 CSAs. For this analysis we construct a perceived competition index composed of variables that measure farmers' perceptions of competition with numerous market outlets and their being constrained in raising their prices due to competitive pressures. Our analysis shows that perceived competition is negatively correlated with CSA farms' profitability, farmers' satisfaction on a number of fronts, various indicators of the social embeddedness of CSA, and two community food security strategies. We conclude that competition is a real, although differential, phenomenon experienced by many CSA farmers in California, and that this competition impacts CSA in ways that undermine some of its commonly held values, especially fair farmer compensation and strong member‐farmer relationships.